1983
DOI: 10.1037/0021-843x.92.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of depressive symptomatology in adult women.

Abstract: Brown and Harris (1978) and Radloff and Rae (1979) have suggested that depression may result from the interaction of precipitating and susceptibility factors. The present study investigated the relationship between depressive symptomatology and a set of demographic and psychosocial variables presumed to be depression-susceptibility factors. A sample of 499 adult women completed the Center for Epidemiologic Studies-Depression Scale (CES-D), a demographic assessment, and measures of four psychosocial variables: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 14 publications
0
26
1
1
Order By: Relevance
“…Reviews of a substantial body of research have not found a consistent relationship between depression and the trait of expressivity (34). Less perceived life control was thought to be associated with increased depressive symptomatology in women in that, as women more often develop "learned helplessness," they are more likely to develop pessimistic explanatory styles (35). However, more recent studies that carefully controlled for a previous history of depression found that there was no significant association between these personality factors and depression (13).…”
Section: Personality Factorsmentioning
confidence: 98%
“…Reviews of a substantial body of research have not found a consistent relationship between depression and the trait of expressivity (34). Less perceived life control was thought to be associated with increased depressive symptomatology in women in that, as women more often develop "learned helplessness," they are more likely to develop pessimistic explanatory styles (35). However, more recent studies that carefully controlled for a previous history of depression found that there was no significant association between these personality factors and depression (13).…”
Section: Personality Factorsmentioning
confidence: 98%
“…Work, however, is also an important institutionalized form of interpersonal contact of relevance to negative affect. Employment per se has been related to lower levels of negative affect and higher self-esteem among women (Kessler & McRae, 1982;Warr & Perry, 1982;Warren & McEachren, 1983). Conversely, negative work conditions are related to higher levels of negative affect among working women (Krause & Geyer-Pestello, 1985), and higher levels of occupational stress predicts later affective disorder in men (Bromet et al, 1988).…”
mentioning
confidence: 88%
“…Par exemple, Warren et al (1983) ont expliqué jusqu'à 39 % de la variance dans les scores relatifs à la dépression de la façon suivante : les facteurs psychosociaux expliquaient 28 % de la variance tandis que 11 points de pourcentages additionnels étaient expliqués par des facteurs démographiques tels que l'éducation et l'âge. Les prédicteurs individuels les plus importants étaient le sens de contrôle sur sa vie (corrélation de -.52) et le soutien social (corrélation de -.29).…”
Section: Dépression Post-partumunclassified